Analysis of the goals scored in Spanish First and Second division during the 2017/2018 season - Raya-González, J.; DJ.,; Domínguez-Díez, M.; Castillo, D. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The aim of the present investigation was to know the typology of the goals scored in Spanish professional soccer through an observational analysis. 1137 goals (508 First division and 629 Second division) scored in 421 soccer matches corresponding to the 2017-2018 season in First and Second division were analyzed. All the goals were classified according to their typology. In general, most of the goals were scored with the legs, at the first touch and from within the area. No significant differences were obtained (p> 0.05) when comparing the typology of goals according to the category of the competition. However, significant differences were observed (p <0.05) when comparing the different playing positions. The results obtained suggest that specific training tasks should be proposed, depending on the playing position, in order to optimize the performance of the players' goal.